2022
DOI: 10.6007/ijarped/v11-i3/14638
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Relationships Between Meaning in Life and Emotional Health among Young Adults of Malaysian Undergraduate Students

Abstract: Emotions are one of the vital aspects in ensuring healthy human functioning and psychological well-being. Thus, this study aims to explore another important psychological element, meaning in life and emotional health among Malaysian university students. This study was carried out using the explorative research design using the quantitative approach. Questionnaires consisted of questions relating to respondents' personal background, meaning in life and emotional health. Trained enumerators distributed questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Likewise, the Meaning factor is important insofar as the more emerging adults experience this psychosocial resource, the lower their levels of depression. This result is similar to the study by Hoesni and Salleh (2022) who also found a negative predictive relationship between meaning in life and depression in a sample of emerging adults. According to the authors, the meaning of life is associated with a clear purpose and significance in life, with the satisfaction derived from this experience being capable of reducing undesirable emotional states.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, the Meaning factor is important insofar as the more emerging adults experience this psychosocial resource, the lower their levels of depression. This result is similar to the study by Hoesni and Salleh (2022) who also found a negative predictive relationship between meaning in life and depression in a sample of emerging adults. According to the authors, the meaning of life is associated with a clear purpose and significance in life, with the satisfaction derived from this experience being capable of reducing undesirable emotional states.…”
Section: Discussionsupporting
confidence: 91%
“…There is no study that has yet developed or validated an instrument to measure ER strategies among Malaysian adolescents in the Malay language. Studies of ER in the Malaysian population are mainly centered on adults [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], and a Malay version of the ERQ which specifically targets adult samples has been developed [ 54 ]. While ER studies have been conducted among Malaysian adolescents [ 55 , 56 , 57 , 58 ], they remain scarce, and it is difficult to draw a reasonable conclusion regarding the development of Malaysian adolescents’ ER.…”
Section: Introductionmentioning
confidence: 99%